Effects of task difficulty manipulation and feedback frequency on dart accuracy in young adults - Azahari, Mohamad Nizam Shah; Mohamed, Muhamad Noor; Raja Hussain, Raja Nurul Jannat; Saiful Annur, Muhamad Safiq; Shari, Maisarah; Md Radzi, Noor Azila Azreen (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Based on the Challenge Point Framework, this study investigates the combined effects of task difficulty manipulation and feedback frequency on dart-throwing accuracy in young adults. While progressive difficulty and appropriately spaced feedback are known to enhance skill acquisition and retention, their interaction in precision-based motor tasks remains under-explored. By examining these variables together, the research seeks to identify the optimal balance of task demand and instructional support to improve motor learning outcomes and inform more effective training interventions.